Urban society - Levine, Myron A. (Annual editions, 2010)
Offers access to a range of articles from some of the most respected magazines, newspapers, and journals. This title features common organizational features useful in the classroom: a general introduction; an annotated table of contents; a topic guide; an annotated listing of selected World Wide Web sites; and a brief overview for each section.